PENGARUH CAPITAL ADUQUECY RATIO, NON PERFOMING LOAN DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL TERHADAP PROFITABILITAS (Jurnal Akuntansi, 2024)
This study analyzes the impact of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Operating Costs to Operating Income (BOPO) on the profitability of 30 banking companies listed on the Indonesia Stock Exchange (2018–2022). Using a quantitative approach and purposive sampling, the research finds that CAR and NPL individually have no significant effect on profitability. Conversely, BOPO significantly influences profitability. Results further indicate that, simultaneously, CAR, NPL, and BOPO exert a significant collective impact on the profitability of the sampled banks during the observed period.